Effect of Sowing Date on Growth and Yield of Local and Imported Maize Varieties (Zea mays L.) - SGAIER, K.; YOUSEF, M. E. (The Libyan Journal of Agriculture, 2023)
A field trial was conducted in 1972 and 1973 on the effect of sowing date on growth and yield of imported and local maize varieties in Tripolitania. Planting dates from April to the middle of July were tested. Total grain yield of both local and imported varieties were greatly reduced by late sowing. The Early American variety yielded from 0.840 to 1.074 tons/ha more than the local variety in both years. Also a significant reduction in yield components and growth parameters was observed in both varieties as a result of late sowing. The local variety was significantly inferior to the Early American in respect to all growth and yield components tested.